2009
DOI: 10.1002/nem.734
|View full text |Cite
|
Sign up to set email alerts
|

Using virtual topologies to manage inter‐domain QoS in next‐generation networks

Abstract: SUMMARYRecently, several computer fi elds have turned to virtualization as a way to simplify complex problems. In this context, the Virtual Topology Service (VTS) was created to manage the advertisement and acquisition of virtual topologies (abstractions of the network status of a domain) and their use in inter-domain resource reservation to provide end-to-end quality of service (QoS). As an effort to create new network architectures which could attend current requirements like mobility and context-aware appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In IP-over-WDM network scenarios, IP routers are the major power consumers in the backbone network [13]; hence, if we are able to reconfigure the virtualized backbone topology in order to bypass them it is possible to minimize network energy consumption by adopting design approaches such as those proposed elsewhere [13,20] for VM placement in the data centers. It is worth noting that network virtualization is to accommodate the high volume of data transmission between the end-to-end virtual services [24] and support end-to-end quality of service [25]. Furthermore, data center network virtualization has several advantages such as QoS support, ease of deployment and management, as well as resilience against security threats for cloud systems [26].…”
Section: Main Design Guidelines and System Modelmentioning
confidence: 99%
“…In IP-over-WDM network scenarios, IP routers are the major power consumers in the backbone network [13]; hence, if we are able to reconfigure the virtualized backbone topology in order to bypass them it is possible to minimize network energy consumption by adopting design approaches such as those proposed elsewhere [13,20] for VM placement in the data centers. It is worth noting that network virtualization is to accommodate the high volume of data transmission between the end-to-end virtual services [24] and support end-to-end quality of service [25]. Furthermore, data center network virtualization has several advantages such as QoS support, ease of deployment and management, as well as resilience against security threats for cloud systems [26].…”
Section: Main Design Guidelines and System Modelmentioning
confidence: 99%
“…Reference [12] proposed a method of mapping the Long Term Evolution (LTE) QoS parameters in order to improve the quality of experience of the end-user when an e-learning application was deployed over a LTE network. The Virtual Topology Service (VTS) [13] showed that one can simply study the process of QoS class mapping by imagining a virtue plane Wang Zai-jian (1)(2) , Yu-ning Dong (1) , Hai-xian Shi (3) , and Zhang Hui (1) ( [14] presented an asymmetric QoS mapping mechanism in the handover between terrestrial and satellite networks which reduces handover blocking probability. Reference [15] proposed a novel end-to-end QoS guaranteed approach in Cognitive Mobile Ad hoc Networks (MANETs), in which a "black box" concept is adopted and end-to-end QoS condition is reflected by some typical QoS parameters.…”
Section: Related Workmentioning
confidence: 99%